Simultaneous identification of multiple animal-derived components in meat and meat products by using MNP marker based on high-throughput sequencing - Yan Yi; Zhanyue Jiang; Lixia Ma; Xiaoni Hou; Lun Li; Deping Ye; Juanlan Du; Hai Peng; Guoquan Han; Huaiping Li; Jiangwen Tang; Lihua Zhou (Food Science and Human Wellness)
In order to save manpower and time costs, and to achieve simultaneous detection of multiple animal-derived components in meat and meat products, this study used multiple nucleotide polymorphism (MNP) marker technology based on the principle of high-throughput sequencing, and established a multi-locus 10 animal-derived components identification method of cattle, goat, sheep, donkey, horse, chicken, duck, goose, pigeon, quail in meat and meat products. The specific loci of each species could be detected and the species could be accurately identified, including 5 loci for cattle and duck, 3 loci for sheep, 9 loci for chicken and horse, 10 loci for goose and pigeon, 6 loci for quail and 1 locus for donkey and goat, and an adulteration model was established to simulate commercially available samples. The results showed that the method established in this study had high throughput, good repeatability and accuracy, and was able to identify 10 animal-derived components simultaneously with 100% repeatability accuracy. The detection limit was 0.1% (m/m) in simulated samples of chicken, duck and horse. Using the method established in this study to test commercially available samples, 4 samples from 14 commercially available samples were detected to be inconsistent with the labels, of which 2 did not contain the target ingredient and 2 were adulterated with small amounts of other ingredients.